HUBUNGAN SISTEM PENGENDALIAN INTERN DAN PARTISIPASI ANGGARAN TERHADAP KINERJA ANGGARAN PT XYZ - Safri Safri; Iswandir Iswandir (JURNAL MITRA MANAJEMEN, 2022)
This study aims to determine the relationship between Budget Performance at PT XYZ, with the free variability of the Internal Control System and Budget Participation. Descriptive and quantitative analysis is used as a technique in analyzing research with linear regression tests for partial t-tests and simultaneous F tests, all populations are made respondents as many as 60 employees, questionnaire data uses a linkers scale. The SPSS 28 test equipment, with the test results t variable x1 showing a calculated value of 3.317 > ttabel = 1.879, explaining the internal control variables related positively and significantly to budget performance, the results of the variable test X2, obtained t count = 3.817 > ttabel 1.879, explained that the variable budget participation is positively and significantly related to budget performance From the F result, the calculated F value = 23.626 > F table 3.87, explains that internal control and budget participation are positively related and sympathetic to budget performance. From the results of the R Square Test obtained a value of 66%. Explaining that the relationship of X1, X2 to Y can be explained as low as 66%, the remaining 34% are related to factors that were not studied in this study. Key Words: Budget, Performance, internal control